2019
DOI: 10.1051/matecconf/201925206006
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven monitoring of the gearbox using multifractal analysis and machine learning methods

Abstract: Data-driven diagnostic methods allow to obtain a statistical model of time series and to identify deviations of recorded data from the pattern of the monitored system. Statistical analysis of time series of mechanical vibrations creates a new quality in the monitoring of rotating machines. Most real vibration signals exhibit nonlinear properties well described by scaling exponents. Multifractal analysis, which relies mainly on assessing local singularity exponents, has become a popular tool for statistical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…It can be seen that its shape differs from the parabolic one, which is typical for multifractal objects. Similar forms of multifractal spectrum are presented in the works of other authors [37][38][39]. According to the graph of the generalized Hurst exponent (Figure 9), it can be seen that the acoustic signals of a defective pipeline are characterized by a pronounced nonlinear dependence h(q).…”
Section: Signal Analysis Using the Mf-dfa Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…It can be seen that its shape differs from the parabolic one, which is typical for multifractal objects. Similar forms of multifractal spectrum are presented in the works of other authors [37][38][39]. According to the graph of the generalized Hurst exponent (Figure 9), it can be seen that the acoustic signals of a defective pipeline are characterized by a pronounced nonlinear dependence h(q).…”
Section: Signal Analysis Using the Mf-dfa Methodssupporting
confidence: 75%
“…It can be seen that its shape differs from the parabolic one, which is typical for multifractal objects. Similar forms of multifractal spectrum are presented in the works of other authors [37][38][39]. With the appearance of a leak in the pipeline, the width of the multifractal spectrum increases, they acquire a parabolic shape and shift along the axis of the abscissa (Figure 12).…”
Section: Signal Analysis Using the Mf-dfa Methodssupporting
confidence: 72%
“…Compared to previous papers [48], the experiment was extended with addit termediate operating states and the analysis method was modified. Vibration acceleration signals were recorded for a rotational speed of about 1 and a load of 12%-pressure 0.6 MPa.…”
Section: Gear Transmission Vibration Signal Analysis On a Laboratory Standmentioning
confidence: 99%
“…The signals presented in the graph represent a si degree of damage, and their characteristic features are visible. Compared to previous papers [48], the experiment was extended with additional intermediate operating states and the analysis method was modified.…”
Section: Gear Transmission Vibration Signal Analysis On a Laboratory Standmentioning
confidence: 99%
“…Artificial Neural Networks (ANN) can work easily with non-linearly separable data, and this makes them ideal for applications such as fault detection and classification, where the training data are sparse, and the network will have to generalize well. Several applications have demonstrated that a neural network can successfully recognize and classify different faults in a number of different condition monitoring applications [16][17][18][19][20][21][22]. A good general introduction to neural networks is provided by [23,24].…”
Section: Fault Classification With Artificial Neural Networkmentioning
confidence: 99%